Improving Palliative Care Team Meetings: Structure, Inclusion, and "Team Care". (July 2016) - Brennan, Caitlin W.; Kelly, Brittany; Skarf, Lara Michal; Tellem, Rotem; Dunn, Kathleen M.; Poswolsky, Sheila
Increasing demands on palliative care teams point to the need for continuous improvement to ensure teams are working collaboratively and efficiently. This quality improvement initiative focused on improving interprofessional team meeting efficiency and subsequently patient care. Meeting start and end times improved from a mean of approximately 9 and 6 minutes late in the baseline period, respectively, to a mean of 4.4 minutes late (start time) and ending early in our sustainability phase. Mean team satisfaction improved from 2.4 to 4.5 on a 5-point Likert-type scale. The improvement initiative clarified communication about patients' plans of care, thus positively impacting team members' ability to articulate goals to other professionals, patients, and families. We propose several recommendations in the form of a team meeting "toolkit."